THE ROLE OF ETHICAL CLIMATE AS A MEDIATOR IN THE LINK BETWEEN ETHICAL LEADERSHIP AND EMPLOYEE BEHAVIOR - Dr.S.Pavithra, Dr.G.Barani, Dr.R.Srikala, Dr.T.Dheepa (South Eastern European Journal of Public Health, 2025)
The research examines the relationship between ethical leadership and employee behavior, focusing on how an ethical climate mediates this connection. Ethical leadership, which promotes integrity, transparency, and accountability, is known to positively influence employee conduct. However, the study suggests that this effect is strengthened when an ethical climate exists within the organization. An ethical climate fosters a work environment where moral behavior is encouraged and valued, creating a culture of trust and accountability that aligns with organizational values.Using data from employees across various industries, the study found that the ethical climate significantly mediates the relationship between ethical leadership and positive employee behaviors. When employees perceive their workplace as ethical, the positive effects of ethical leadership are amplified, leading to increased integrity, trust, and commitment. The research highlights that organizations should focus on both cultivating ethical leaders and creating an ethical climate to maximize the benefits of ethical leadership and foster better employee behavior.